Dhurrin: a potential endogenous nitrogen turnover source for early seedling growth in sorghum - Emendack, Yves; Sanchez, Jacobo; Laza, Haydee (Frontiers in Plant Science, 2025)
Dhurrin is a cyanogenic glucoside found in all vegetative tissues of Sorghum bicolor, functioning as a herbivore repellent, antifungal agent, osmoprotectant, and nitrogen (N) storage. Dhurrin concentration is usually highest in young seedlings, where it rapidly accumulates following germination, after which its biosynthesis decreases and its turnover increases as the seedling ages. To avoid prussic acid poisoning from dhurrin catabolism in cattle grazing or foraging on sorghum, numerous research studies now focus on breeding for dhurrin-free or acyanogenic sorghum using EMS (Ethyl methanesulfonate) mutants with a non-functional dhurrin biosynthetic pathway. However, there has been limited and conflicting research investigating the role dhurrin plays as a potential nitrogen source in sorghum’s early seedling growth, especially under N deficiency. It is plausible that the presence of background mutations in dhurrin-free sorghum mutants could mask or confound how the absence of dhurrin affects early seedling growth. Using a naturally occurring (non-mutant) ultra-low dhurrin genotype and known low and high dhurrin genotypes, the current research investigated the importance of dhurrin as a potential endogenous nitrogen source for early seedling growth in simulated non-marginal (N-available) and marginal (N-deficient) media. Dhurrin was implicated to be an N source for seedling growth from 8 to 13 days after planting under deficient N conditions. In N-deficient media at 13 days after planting, high-dhurrin-level genotypes accumulated more seedling fresh shoot biomass than low-dhurrin-level genotypes. Thus, while acyanogenic sorghum will be beneficial in expanding sorghum’s economic value, the use of dhurrin knock-out mutants can prove problematic since the complete lack of dhurrin may affect field germination and stand establishment, particularly under N-deficient or low-N-input conditions.